Climate-mediated upward shift of coffee agroforestry and associated reforestation in Arabica coffee’s native range - Firew Bekele Abebe; Kristoffer Hylander; Sileshi Nemomissa; Tamrat Bekele; Beyene Zewdie; Ayco J M Tack (Stockholm University, 2026)
Climate change is expected to cause latitudinal and elevational shifts in where crops can grow, with major consequences for land use, rural livelihoods and biodiversity. Shifts in agroforestry systems can be especially transformative, as this alters tree cover. We used semi-structured interviews and vegetation surveys to investigate the patterns, drivers, consequences and future trajectories of an upward shift of Arabica coffee agroforestry within its native range in the Afromontane mountains. We observed a climate-, income- and crop raiding-driven upward shift of coffee production into a novel elevational range, with positive feedback mechanisms enhancing the future adoption of agroforestry. Forest and open-land-derived agroforests showed similar woody plant species richness and large overlaps in community composition. Open-land-derived coffee agroforestry is, and is expected to increasingly be, the dominant coffee agroforestry type in the novel range, with positive implications for tree cover, biodiversity and ecosystem services in one of the world’s biodiversity hotspots.
Keywords: Metadata; METADATA; Biological Sciences; Biologi